Proposal of a coupled DDA-SPH method incorporating a new contact algorithm for soil-structure interaction simulations in geotechnical hazards - Peng, Xinyan; Yu, Pengcheng; Zhu, Hui; Cheng, Xiao; Zhang, Yingbin; Li, Changze (Computers and geotechnics, 2023)
Accurate description of soil-structure interaction problems in geotechnical hazards is challengeable. A coupled method is a potential approach to solve such problems. Discontinuous deformation method (DDA) can be used to describe structure behavior and smoothed particle hydrodynamics (SPH) suits well for capturing soil behavior; meanwhile, the coupled DDA-SPH method can simulate complex soil-structure interaction through a contact algorithm. In the original contact algorithm, a penalty method using the Mohr-Coulomb failure criterion is utilized to embody the interaction forces. However, five calculation parameters are involved and should be chosen carefully. Moreover, the energy dissipation cannot be considered quantitatively and suitably. To overcome these drawbacks, a new contact algorithm is proposed in this study. This new contact algorithm can consider the friction and energy dissipation at contacts between DDA blocks and SPH particles using two physical parameters (including the interface friction angle and coefficient of restitution). Several validation examples were carried out to investigate the performance of the newly coupled DDA-SPH method. The simulated results were compared with theoretical solutions or those obtained by other different numerical methods, which shows good agreements. This suggests that the newly coupled DDA-SPH method can be applied to conduct the soil-structure interaction simulations with ease.